2015
DOI: 10.1097/hmr.0000000000000017
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between voice climate and patients’ experience of timely care in primary care clinics

Abstract: Background-Aspects of the patient care experience, despite being central to quality care, are often problematic. In particular, patients frequently report problems with timeliness of care. As yet, research offers little insight on setting characteristics that contribute to patients' experience of timely care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Second, as would be expected, voice climate research has cast voice behavior as the primary outcome, at both the individual and group level (Frazier & Bowler, 2015;Morrison et al, 2011). Although this is consistent with the climate literature, that climate for something predict specific outcomes (Schneider et al, 1998), there is evidence that voice climate may predict other outcomes (e.g., Nembhard et al, 2015). Contributing to this body of research that broadens the predictive network of voice climate, our results indicate that voice climate is positively related to team decision-making effectiveness and team innovative performance.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Second, as would be expected, voice climate research has cast voice behavior as the primary outcome, at both the individual and group level (Frazier & Bowler, 2015;Morrison et al, 2011). Although this is consistent with the climate literature, that climate for something predict specific outcomes (Schneider et al, 1998), there is evidence that voice climate may predict other outcomes (e.g., Nembhard et al, 2015). Contributing to this body of research that broadens the predictive network of voice climate, our results indicate that voice climate is positively related to team decision-making effectiveness and team innovative performance.…”
Section: Discussionmentioning
confidence: 51%
“…For example, Frazier and Fainshmidt (2012) found that voice climate was positively related to customer service performance. Furthermore, recent research by Nembhard, Yuan, Shabanova, and Cleary (2015) found that higher voice climate perceptions among front-line health care staff were positively related to the timeliness of patient care. To our knowledge, only one published study has explored the antecedents to voice climate, which showed that supervisor undermining was negatively related to voice climate (Frazier & Bowler, 2015).…”
Section: Tmx and Team Voice Climatementioning
confidence: 99%
“…On a more local level, healthcare organizational structures influence patient experience. Professionals in a hierarchical structure felt more or less empowered and valued dependent on their position in the hierarchy . Nembhard et al studied patient‐reported timeliness of care, finding significant improvement in patient experience survey results from healthcare organizations employing horizontal structures.…”
Section: Resultsmentioning
confidence: 99%
“…Our measures of care team functions (phone communication, in-person communication, and care coordination) do not represent the entirety of important care team functions. Successful care teams must also achieve good internal communication and trust among team members, must have a clear and shared understanding of individual roles and responsibilities, and must do other important work as a team that may be less visible to patients (Nembhard, Yuan, Shabanova, & Cleary, 2015; True et al, 2013). Future research could address how these and other care team functions not measured in this study influence ratings of access to care.…”
Section: Discussionmentioning
confidence: 99%